Selection of cDNAs differential fragments related to water stress in Ullucus tuberosus Loz. (Bassellaceae) «olluco» - Romero-Carpio, Mariela (2005)
Thirty-one differential fragments of cDNA related to drought tolerance have been selected from the mRNA differential expression of in vitro plantelets belonging to two accessions of Ullucus tuberosus Loz. «olluco» highly tolerant to osmotic stress.